EMBODIMENT OF ARBITRARY ABBREVIATIONS AND ACRONYMS IN INSTAGRAM SOCIAL MEDIA - Verlin, Sri (Journal of Islam and Science, 2018)
This study aims (1) to describe the embodiment of arbitrary abbreviations and acronyms in Instagram social media, and (2) explains the purpose of forming arbitrary abbreviations and acronyms in Instagram social media. The method used in this study is observed method by taking screenshots and recording abreviation data. The sample used in this study does not depend on quantity, but rather on quality based on the scope andprofundity of the problem researched. The results show that arbitrary abbreviations are made by twisting and forming a new extension. Meanwhile, the acronym is made for an extension that seems forced because the form of the acronym does not have a meaning relationship with its extension. Arbitrary abbreviations and acronyms generally also contains meaning that was deliberately mischarged, making it difficult for understanding outsiders who don't use social media.There are three objectives of forming arbitrary abbreviations and acronyms on Instagram social media, looks contemporary, ragged material, and as a reminder.